Pengaruh Motivasi, Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Inspektorat Mataram - Verdi; Syaiful Amri; Rosyia Wardani (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to examine the influence of motivation, workload and work environment on the performance of Mataram Inspectorate employees. The population of this study is all employees of the Mataram Inspectorate. The sampling method uses the purposive sampling technique method with a sample of 54 employees with questionnaire distribution. Based on the results of the t-test test, motivation (X1) with a sig value of 0.338 > 0.05, while the t-value calculated is 0.966 < 2.008, meaning that motivation has a non-significant effect on employee performance. Workload (X2) with a sig value of 0.001 < 0.05, while a t-value of 3.620 > 2.008 means that workload has a significant effect on employee performance. Meanwhile, the work environment (X3) with a sig value of 0.377 > 0.05, while the t-value of -0.892 < 2.008 had a negative and insignificant effect on employee performance. Based on the results of the f test, workload motivation, and work environment had a simultaneous effect on employee performance with an f value calculated > table of 5.497 > 2.79 with a significant level of 0.002 < 0.05. The most dominant variable that affects employee performance is the workload variable (X2) of 3,620